(untitled) (Prostor, 2023)
Derelict, dilapidated buildings in various states of ruin have always been present in our built environment. Theoretical approaches to the issue of ruins within the field of architecture have been changing continuously in response to shifting social, political, economic, and cultural conditions. Although origins of the debates on ruins can be traced centuries back, the topic came into focus with renewed intensity following the mass destruction in the wake of World War II. This paper discusses relevant perspectives on the phenomenon of decay in architecture from the 1950s to the 2020s, and offers a critical synthesis of their diverse viewpoints, thus enabling further formulations of contemporary positions and design strategies concerning this increasingly significant subject matter.